2019
DOI: 10.1038/s41531-019-0084-6
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of exocytosis and mitochondrial relocalization by Alpha-synuclein in a mammalian cell model

Abstract: We characterized phenotypes in RBL-2H3 mast cells transfected with human alpha synuclein (a-syn) using stimulated exocytosis of recycling endosomes as a proxy for similar activities of synaptic vesicles in neurons. We found that low expression of a-syn inhibits stimulated exocytosis and that higher expression causes slight enhancement. NMR measurements of membrane interactions correlate with these functional effects: they are eliminated differentially by mutants that perturb helical structure in the helix 1 (A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
55
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(70 citation statements)
references
References 104 publications
15
55
0
Order By: Relevance
“…Upon the binding of SVs, αS has a tendency to promote their clustering [12][13][14]17 , a process that has been associated with the maintenance of SV pools at the synaptic termini 11,[18][19][20] . Additionally, αS has been shown to influence the regulation of the vesicle trafficking from the endoplasmic reticulum (ER) to the Golgi 13,20 , and to localise at mitochondrial membranes, where it has been proposed to mitigate the effects of oxidative stress [21][22][23][24] . All these putative functions by αS require its binding to biological membranes 25,26 , a central interaction that defines the relevant biological form of αS in vivo 27 and influences the kinetics of its aggregation 11,28,29 , as well as the toxicity of its aggregates 1,30,31 .…”
mentioning
confidence: 99%
“…Upon the binding of SVs, αS has a tendency to promote their clustering [12][13][14]17 , a process that has been associated with the maintenance of SV pools at the synaptic termini 11,[18][19][20] . Additionally, αS has been shown to influence the regulation of the vesicle trafficking from the endoplasmic reticulum (ER) to the Golgi 13,20 , and to localise at mitochondrial membranes, where it has been proposed to mitigate the effects of oxidative stress [21][22][23][24] . All these putative functions by αS require its binding to biological membranes 25,26 , a central interaction that defines the relevant biological form of αS in vivo 27 and influences the kinetics of its aggregation 11,28,29 , as well as the toxicity of its aggregates 1,30,31 .…”
mentioning
confidence: 99%
“…apoptosis (12). Recent findings substantiate this notion by revealing direct interactions between aSyn and mitochondrial membranes and lipids (13,14), aSyn-induced organelle toxicity (15, 16,Mahul-Mellier, 2020 #93), stress-related re-localization of aSyn to mitochondria (17,18) and pathological colocalization with mitochondria (and other non-proteinaceous structures) in brain-derived LB inclusions (5) and cellular models of LB formation and maturation (4). In addition, the functions of many other Parkinson's disease proteins converge on mitochondria and are directly linked to mitochondrial biology (19).…”
Section: Introductionmentioning
confidence: 85%
“…The SNAREs, syntaxin-1, SNAP-25, and synaptobrevin-2, are shown in red, gray, and blue, respectively. JBC REVIEWS: Protein disorder in vesicle traffic and release 119,[122][123][124][125][126][127][128][129][130][131][132][133]. It has further been suggested that synuclein may also function as a molecular chaperone for synaptobrevin-2, the synaptic v-SNARE (119).…”
Section: ␣-Synucleinmentioning
confidence: 99%
“…lipids with phosphatidylethanolamine headgroups) (162)(163)(164)(165)(166)(167). Synuclein thus may be optimized to bind synaptic vesicles, although it clearly interacts with other membranes as well, including possibly the plasma membrane and mitochondrial membranes (115,116,133). Interestingly, synuclein can, in some contexts, actively induce membrane curvature to remodel lipid membranes; this could have functional significance for synaptic vesicle exocytosis, which requires alterations in membrane shape and curvature prior to membrane fusion (168 -171).…”
Section: ␣-Synucleinmentioning
confidence: 99%
See 1 more Smart Citation